2015
DOI: 10.1038/srep11642
|View full text |Cite
|
Sign up to set email alerts
|

Function and evolution of Magnaporthe oryzae avirulence gene AvrPib responding to the rice blast resistance gene Pib

Abstract: Magnaporthe oryzae (Mo) is the causative pathogen of the damaging disease rice blast. The effector gene AvrPib, which confers avirulence to host carrying resistance gene Pib, was isolated via map-based cloning. The gene encodes a 75-residue protein, which includes a signal peptide. Phenotyping and genotyping of 60 isolates from each of five geographically distinct Mo populations revealed that the frequency of virulent isolates, as well as the sequence diversity within the AvrPib gene increased from a low level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
151
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(158 citation statements)
references
References 55 publications
6
151
1
Order By: Relevance
“…The transposable element (TE) insertion in the last exon of the ACE1 gene (Fudal et al ., ) and Pot3 inserted in AVR‐Pizt and AVR‐Pita1 (Kang et al ., ; Zhou et al ., ; Li et al ., ) resulted in new virulent alleles. DNA sequence analysis of the AVR‐Pib allele in a set of 108 diverse blast isolates revealed that TE insertion (frequency 81.7%), segmental deletion (11.1%), complete absence (6.7%) and point mutation (0.6%) all lead to losses of the avirulence function (Zhang et al ., ). Aligning 16 AVR‐Pib alleles identified seven functional nucleotide polymorphisms in the AVR‐Pib genes that are correlated with three distinct expression profiles (Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The transposable element (TE) insertion in the last exon of the ACE1 gene (Fudal et al ., ) and Pot3 inserted in AVR‐Pizt and AVR‐Pita1 (Kang et al ., ; Zhou et al ., ; Li et al ., ) resulted in new virulent alleles. DNA sequence analysis of the AVR‐Pib allele in a set of 108 diverse blast isolates revealed that TE insertion (frequency 81.7%), segmental deletion (11.1%), complete absence (6.7%) and point mutation (0.6%) all lead to losses of the avirulence function (Zhang et al ., ). Aligning 16 AVR‐Pib alleles identified seven functional nucleotide polymorphisms in the AVR‐Pib genes that are correlated with three distinct expression profiles (Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…DNA sequence analysis of the AVR‐Pib allele in a set of 108 diverse blast isolates revealed that TE insertion (frequency 81.7%), segmental deletion (11.1%), complete absence (6.7%) and point mutation (0.6%) all lead to losses of the avirulence function (Zhang et al ., ). Aligning 16 AVR‐Pib alleles identified seven functional nucleotide polymorphisms in the AVR‐Pib genes that are correlated with three distinct expression profiles (Zhang et al ., ). These findings demonstrated that M. oryzae uses the transposons to change the expression of AVR genes in breaking down R genes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a recent survey of an AVR locus comprising 108 Magnaporthe oryzae isolates, 81% of AvrPib polymorphisms leading to loss of avirulence resulted from TEs, whereas loss of avirulence due to SNPs was rare (0.6%; ref. 50). Thus, including information on SNPs, structural gene/transcript variants, and presence/absence of genes/transcripts in association studies is expected to significantly improve the identification of candidate AVR genes in eukaryotic filamentous pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of effectors have been identified in M. oryzae which facilitate feeding on both living and dead plant tissues. These effectors include AvrPi54, Avr-Pia, Avr-Pii, Avr-Pik/ km/kp, Avr-Pita, Pwl1, Pwl2, Bas2, Avr-Piz-t, Avr-Pi9, Avr-Pib, Iug6, Iug9 and Slp1 (Dong et al, 2015;Khang et al, 2010;Mentlak et al, 2012;Oliveira-Garcia and Valent, 2015;Ray et al, 2016;Wu et al, 2015;Yoshida et al, 2009;Zhang and Xu, 2014;Zhang et al, 2015). Other studies have started to characterize plant cell death-inducing effectors in M. oryzae (Chen et al, 2013) and the rice false smut fungus, Ustilaginoidea virens (Fang et al, 2016).…”
Section: Identification Of Fungal Effectorsmentioning
confidence: 99%